Social work and geriatric services - Palmer, Sharon Duca , 1965- (Oakville, Ontario : Apple Academic Press, 2011)
Geriatric services in social work deals with the care of the elderly in many facets. This book addresses many of the important topics in social work with the elderly, including chronic disease prevalence, conducting research with older people, cognitive functioning and social integration, exercise for the elderly, health screening, and more
Includes bibliographical references and index
Keywords: Medical social work; Social work with older people